Application of green quality function deployment and fuzzy theory to the design of notebook computers. Issue 4 (3rd July 2016) - Ko, Ya-Chuan; Lo, Chi-Hung
Abstract: In the era of advancing technology and information explosion, portable electronic products such as notebook computers have become one of the indispensable parts in our daily lives due to their high portability. In recent years, notebook computer models are renovated in a faster pace and the time-to-market for a new model is just three to four months. According to statistics, in average people buy a new laptop to replace the old one every three years. It is known that a laptop is another electronic product with a short life cycle. To reduce the impact of discarded laptops to the environment, it is required to consider the recycling approach during the design stage so that the materials can be re-used. This study applied the green quality function deployment (GQFD) approach to convert the product attributes that are valued by customers into design attributes of the product during the stages of production process, usage, packaging and disposal by the green life cycle design (GLCD) concept. In addition, triangular fuzzy numbers were used to express the intensity of relationship between product attributes and design attributes. Finally, the product attributes that are valued by customers can be determined by the relationship matrix of quality development for laptops and they serve as the design reference during the design stage. The results of the case study on laptops indicated that, consumers value more on product characteristics of "re-cycle for re-use", "zero environmental pollution", "scratch-resistant", "hard drive capacity", "convenient portability", "display" and "price". These consumer opinions were converted into engineering characteristics via each stage of GLCD with the assumption that the future market for laptops is optimistic (optimism index a = 0.8). The results obtained by calculation indicated that, the top five engineering characteristics are "processor speed", "stand-alone graphics card", "screen resolution", "material" and "recycling". Some suggestions and aspects were raised on these characteristics as a reference for manufacturers when developing new laptop models.